Cultural Change in Post-Migrant Societies Re-Imagining Communities Through Arts and Cultural Activities - Sievers, Wiebke (IMISCOE Research Series,, 2024)
This open access book links the artistic and cultural turn in migration studies to the larger struggle for narrative and cultural change in European migration societies. It proposes theoretical and methodological approaches that highlight how ideas of change expressed in artistic and cultural practices spread and lead to wider cultural change. The book also looks at the slow processes of change in large cultural institutions that emerged at a time when culture was nationalised. It explains how individual and group activities can have an impact beyond their immediate surroundings. Finally, the book discusses how migration researchers have cooperated with arts and cultural producers and used artistic means to increase the effect of their research in the wider public. As such, the book provides a great resource for graduate students and researchers in the social sciences and the humanities who have an interest in migration studies and want to move beyond interpreting the world towards changing it.